HEPATITIS B VIRUS MARKERS AMONG PREGNANT WOMEN IN SAUDI ARABIA - Ikram, M. Hafeez (Journal of Ayub Medical College Abbottabad, 1990)
Hepatitis B surface antigen (HBsAg) among women varies from 3.8% in Riyadh area to 15% in Khaiber.1 HBsAg carrier mother may deliver a baby, which has a greater chance of becoming a HBsAg carrier.2 Hepatitis Delta virus (HDV) infections occur along with HB V infections as coinfections or superinfections.3 In order to find the risk to the baby, pregnant women were surveyed for the presence of Hepatitis B virus (HBV) and HDV markers.